Estudo fitoquímico da casca do caule e folhas da espécie Rhamnidium elaeocarpum Reissek (rhamnaceae) e avaliação das atividades biológicas - Kauffmann, Angélica Correa (2020)
The Rhamnaceae family is found in tropical and subtropical regions of the terrestrial globe, composed of 58 genera with approximately 900 species, and in Brazilian territory are found 47 species in 12 genera. The species Rhamnidium elaeocarpum has a synonym for Rhamnidium cognatum, is found only in South American soil, with a wide distribution from Peru to the east of Brazil and Argentina, popularly known as, Cabrito, Cabriteiro, Bosta de Cabrito, Saguaraji or Cafezinho, and it by popular medicine to reduce pruritus of the gums of children at the beginning of the dentition and for stomach pains. This work describes for the first time the isolation and identification of secondary metabolites in the genus and species Rhamnidium elaeocarpum. Besides we demonstrated the inibitory activity of lipid peroxidation in crude extracts and the inhibitory and enzymatic evaluation of lysosomal proteases B and L in isolated substances. Chrysofanol anthraquinone, anthroneone anthraquinone elaeocarpanthraquinone, the mixture of steroids β-sitosterol and stigmasterol, and glycosylated β-sitosterol saponin were isolated from the stem bark. From the leaves two flavonoids kaempferol and quercetin were isolated. The lipid peroxidation inhibition assay was promising for the crude ethanolic extract of the leaves at concentrations of 50 and 100 µg / mL in mouse liver and kidney tissues. Chrysofanol and elaeocarpanthraquinone were tested in cathepsin B and L inhibition assays, which showed significant, and showed positive cooperativity when the enzyme inhibition mechanism was analyzed. This work contributes significantly to the chemical and biological knowledge of the species, reporting the isolation of secondary metabolites and highlighting important biological activities.